Tanggung Jawab Pidana Pengurus Koperasi Simpan Pinjam Atas Keterlibatan Dalam Tindak Pidana Pemalsuan Surat (Analisis Putusan Pengadilan Negeri Sukoharjo Nomor 111/ Pid.B/2015/PN.Skh) - Tin Sri Mulyawati Rukmana (Jurnal Selat, 2021)
A cooperative is a legal entity that is structured as a joint effort based on the principles of kinship and economic democracy. One of the cooperative organs is the management, which in the management of the cooperative, the management can appoint managers who are given the authority and power to manage the business. The use of the term Manager is intended to cover a broader understanding and provide an alternative for Cooperatives. Thus, according to its interests, the Cooperative can appoint Managers as managers or directors. This study analyzes criminal liability for letter falsification by the management of the Cooperative. The research method used is normative legal research using a statutory approach and a conceptual approach. The results showed that the act of counterfeiting letters carried out by cooperative management could be subject to criminal liability if it was proven and fulfilled all the elements in Article 264 of the Criminal Code in conjunction with Article 64 paragraph (1) of the Criminal Code, namely the existence of a criminal act (against the law), above a certain age can responsible, has a form of error in the form of intentional or negligence and there is no forgiving reason.